2019
DOI: 10.1039/c9cy00419j
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the morphology of Ni–Pt nanocatalysts through the variation of oleylamine and oleic acid: a study on oxygen reduction from synthesis to fuel cell application

Abstract: Systematic study on the variation of morphology, size and composition of Ni–Pt nanoparticles with higher catalytic activity towards oxygen reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…The above strategies result in conductive, stable, and active catalysts in half-cell experiments and in PEMFC tests. One of the first steps in the development of more active catalysts was to form Pt-based alloys, Pt-M type (M = transition metal, e.g., Pt-Au [ 240 ], Pt-Fe [ 241 ], Pt-Ni [ 242 ]) or Pt-MN (M ≠ N e.g., Pt 2 CuNi [ 243 ] or PtNiMo [ 244 ]). Yin et al reported the production of Pt-Au alloy nanoparticles, which not only achieved a more active catalyst than Pt/C, but also explained the effect that the heat treatment has on the structure of nanoparticle, and how this treatment considerably increases the catalytic activity of the bimetallic material.…”
Section: Electrocatalysts and Electrodesmentioning
confidence: 99%
“…The above strategies result in conductive, stable, and active catalysts in half-cell experiments and in PEMFC tests. One of the first steps in the development of more active catalysts was to form Pt-based alloys, Pt-M type (M = transition metal, e.g., Pt-Au [ 240 ], Pt-Fe [ 241 ], Pt-Ni [ 242 ]) or Pt-MN (M ≠ N e.g., Pt 2 CuNi [ 243 ] or PtNiMo [ 244 ]). Yin et al reported the production of Pt-Au alloy nanoparticles, which not only achieved a more active catalyst than Pt/C, but also explained the effect that the heat treatment has on the structure of nanoparticle, and how this treatment considerably increases the catalytic activity of the bimetallic material.…”
Section: Electrocatalysts and Electrodesmentioning
confidence: 99%
“…The reduction rate of Pt precursor (Pt-OAm complex) is much faster than the reduction rate of Ni precursor (Ni-OAm complex) because OAm molecules (hard base) strongly coordinate with Ni 2 + ions (hard acid), forming a strong metal-ligand complex. [40,41] Initially, a high decomposition rate of Pt precursor leads to the supersaturated solution with Pt monomers and Pt nuclei form. As the reaction is progressed further, the concentration of Pt monomers falls due to the rapid depletion of Pt monomer in the nucleation stage, and Ni monomer concentration gradually increases in the solution.…”
Section: Resultsmentioning
confidence: 99%
“…Membrane electrode assemblies (MEAs) and electrocatalytic inks were prepared following the procedure previously described in ref . Briefly, commercial 20% Pt/C Etek nanoparticles and synthesized Ni–Pt/C polyhedral nanoparticles (60% wt Pt) were used as the catalytic material for the anode and cathode, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The performance of MEAs prepared with SPEEK/ZIF membranes was evaluated in a Fuel Cell Test System model 890B, coupled to a Compucell GT humidification system operating with a backup pressure of 30 psi and a 0.08 L min –1 flowrate of H 2 and O 2 for anode and cathode, respectively. An activation protocol using voltage steps was performed following the procedure reported in ref to obtain the polarization curves at different temperatures of the cell in the range of 80–120 °C. An MEA prepared with commercial Nafion 117 membrane was assembled and evaluated under the same conditions for comparison purposes.…”
Section: Methodsmentioning
confidence: 99%